PEMBIASAAN IBADAH SHALAT PADA ANAK USIA DINI DI KB TPA PERMATA RUBY - Syifa Bahrul Ulumuddin; Cucu Atikah; Fahmi Fahmi (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2021)
Every child is born into the world in a fitrah state and has potential to be developed. Children need an early education in the development of religious and moral values to get used to doing their religious worship properly and properly. Habituation of prayer services in early childhood that are routinely performed daily at KB TPA Permata Ruby. The purpose of this research is to know the process of performing the habituation of prayer services, obstacles and solutions. The research method used is by qualitative research approach with descriptive research type or design. The data is analyzed through the data reduction stage, data presentation and draw conclusions. The results showed students perform the habituation of prayer services guided and directed by the accompanying teacher. The obstacles that occur in the implementation of prayer, namely children lack focus and prayer movements are not appropriate, so teachers must help the students.